Negative pressure wound therapy: our experience of a polytrauma with degloving injury - Surya Pratap, Mangipudi; Goel, Mahak; Kundaikar, Janitta; Meena, Kusum (International Surgery Journal, 2024)
Degloving injuries are uncommon serious conditions occurring in high-velocity traumas with high mortality and morbidity. The lack of standard guidelines for the diagnostic and therapeutic management of such injuries provides a challenge to the surgeon. We present a case of a 35-year-old male with an extensive degloving injury who underwent primary closure unsuccessfully. The necrotic area was debrided and negative pressure wound therapy was used for the management of the wound. The patient was managed with split skin grafting and post successful recovery on all fronts has been completely rehabilitated. Though primary suturing is always tried, the viability of the degloved skin remains questionable and might need extensive debridement. Negative Pressure Wound dressing is seen to be accelerating wound healing and improving the treatment outcome.